2017
DOI: 10.1128/genomea.00454-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Recombinant Porcine Reproductive and Respiratory Syndrome Virus Strain from Two Genotype 1 Modified Live Virus Vaccine Strains

Abstract: This paper provides information on the complete genome sequence of a porcine reproductive and respiratory syndrome virus (PRRSV) strain isolated on a French pig farm which was identified as a recombinant strain from two commercial modified live virus vaccine strains of genotype 1 (VP-046BIS and DV strains).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 9 publications
0
21
0
2
Order By: Relevance
“…An experimental study from France revealed that the Porcilis/ Unistrain recombinant virus describe above (Renson et al, 2017) seems to be more virulent than the two parent PRRSV-1 vaccine viruses (Eclercy et al, 2019). However, this study did not assess if the increased virulence of the recombinant virus reflected that the recombinant virus was adapted to swine or if it was a result of the recombination per se.…”
Section: F I G U R Ementioning
confidence: 91%
See 1 more Smart Citation
“…An experimental study from France revealed that the Porcilis/ Unistrain recombinant virus describe above (Renson et al, 2017) seems to be more virulent than the two parent PRRSV-1 vaccine viruses (Eclercy et al, 2019). However, this study did not assess if the increased virulence of the recombinant virus reflected that the recombinant virus was adapted to swine or if it was a result of the recombination per se.…”
Section: F I G U R Ementioning
confidence: 91%
“…In two of these reports, the Unistrain vaccine strain Amervac was part of the recombined virus, but the recombination break point differed from the 'Horsens' virus. Recombination between two PRRSV-1 vaccine strains has only been reported once from France where a recombinant between the 'DV' vaccine strain (Porcilis PRRS, MSD) and the 'Amervac' strain (Unistrain, Hipra) was detected in a single herd (Renson et al, 2017).…”
Section: F I G U R Ementioning
confidence: 99%
“…Therefore, the simultaneous or contemporaneous use of different PRRSV MLV vaccines poses a risk of recombination. Renson et al reported a recombinant PRRSV-1 strain derived from two MLV vaccines (Unistrain PRRS and Porcilis PRRS) in a pig farm in France [ 9 ]. In a later study from the same group, animals infected with the recombinant strain did not show significant clinical signs, although the recombinant strain demonstrated increased excretion and transmission capabilities compared to parental vaccine strains [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Central and Western Europe, only Lelystad virus-like circulates, but in Eastern Europe, all subtypes are present [6]. The PRRS virus genome is not segmented, having a positive polarity and size of about 15 kb [7]. The genome contains 8 open reading frames (ORF) for encoding structural and non-structural proteins of the virus.…”
Section: Introductionmentioning
confidence: 99%